1984
DOI: 10.1203/00006450-198408000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Role of Arginine Vasopressin in Blood Pressure Control in Young Rats

Abstract: SummaryWe investigated the importance of arginine-vasopressin (AVP) for blood pressure control in young and adult rats. Most of the studies were performed on Brattleboro rats with complete diabetes insipidus (DI). In some protocols, Sprague-Dawley rats (SD) were also used. The rats were age 20-24 days (young) or 50-80 days (adult). Adult DI rats have a significantly higher mean arterial pressure (MAP) than adult SD rats. The studies were performed during normovolemia and hypovolemia. Hypovolemia was created by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
1988
1988

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…During hypovolemia AVP is of great importance for the maintenance of the arterial blood pres sure. The effect of AVP on the arterial pres sure during hypovolemia is at least as pro nounced in infant as in adult rats [11]. We have therefore suggested that the high AVP levels in the perinatal period are of major importance for the control of blood pressure and regional blood flow and of minor impor tance for water balance.…”
mentioning
confidence: 90%
“…During hypovolemia AVP is of great importance for the maintenance of the arterial blood pres sure. The effect of AVP on the arterial pres sure during hypovolemia is at least as pro nounced in infant as in adult rats [11]. We have therefore suggested that the high AVP levels in the perinatal period are of major importance for the control of blood pressure and regional blood flow and of minor impor tance for water balance.…”
mentioning
confidence: 90%
“…A potent vasoconstrictive activity of AVP on several vascular beds has been observed in both adult and fetal mammals (Iwamoto, Rudolph, Keil & Heymann, 1979). It has also been suggested that the haemodynamic effects of AVP are of more importance at an early age than later in life (Herin, Eklof & Aperia, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the haemodynamic effects of AVP are of more importance at an early age than later in life (Herin, Eklof & Aperia, 1984).…”
Section: Introductionmentioning
confidence: 99%